Seasonal dominance of CL500‐11 bacterioplankton (phylum Chloroflexi) in the oxygenated hypolimnion of Lake Biwa, Japan. Issue 1 (20th August 2012) - Okazaki, Yusuke; Hodoki, Yoshikuni; Nakano, Shin‐ichi
Abstract Uncultured bacteria affiliated with the CL500‐11 cluster (phylum Chloroflexi) were first reported from the oxygenated hypolimnion of Crater Lake (USA) as a predominant bacterioplankton, although this dominance has not been reported in other environments. In this study, we showed that CL500‐11 is also dominant in the oxygenated hypolimnion of Lake Biwa (Japan) and followed its spatiotemporal succession using fluorescent in situ hybridization. CL500‐11 cells were almost absent [< 1% of 4′, 6‐diamidino‐2‐phenylindole (DAPI)‐stained cells] at the beginning of the stratification period, dominated (> 10% of DAPI‐stained cells; maximum = 16.5%) in the hypolimnion during the stratification period, and decreased to below the detection limit with the collapse of the thermocline. This pattern was observed over two annual cycles. A longitudinal assessment also showed that CL500‐11 was the dominant bacterium in the hypolimnion over the whole lake, but was generally undetectable in the stratified epilimnion. These data suggest that CL500‐11 is acclimated to the oxygenated hypolimnion and is a potentially important component of the pelagic biogeochemical cycling of the lake. A comparative analysis of 16S rRNA gene sequences revealed that almost all CL500‐11 sequences previously deposited in the database were detected from hypolimnion or holomictic water in deep oxic freshwater lakes, suggesting that the bacteria may form one of the common lineages residing in an aerobic hypolimnetic niche.